1915 N.M. Law 153, ch. 101, §7. - (:unkn) unknown (General Publisher, 1915)
No person shall at any time shoot, hunt or take in any manner any wild animals or birds or game fish as herein defined in this state without first having in his or her possession a hunting license as hereinafter provided for the year in which such shooting, fishing or hunting is done. The presence of any person in any open field, prairie or forest, whether enclosed or not with traps, gun or other weapon for hunting, without having in possession a proper hunting license as herein provided, shall be prima facie evidence of the violation of this section.
--
Keywords: HUNTING REGULATION